Seismic repair of severely corroded precast RC columns with FRP shell and headed steel bars - Sayal Shrestha; Chris P. Pantelides (Journal of Infrastructure Preservation and Resilience)
Abstract Corrosion of reinforced concrete bridge columns degrades their seismic performance. A seismic repair strategy for severely corroded reinforced concrete columns is developed. Three specimens were constructed; one served as the control, and two were corroded with a 25% target mass loss of longitudinal steel bar area. The control and one of the corroded columns were tested under cyclic loads, and the remaining corroded column was repaired before being tested. Repair consisted of a carbon fiber reinforced polymer shell filled with concrete and connected to the footing using headed steel bars. All three columns failed due to longitudinal steel bar fracture; the control column failed at 9.0% drift ratio, the severely corroded column failed at 6.0% drift ratio after longitudinal steel bars buckled, and the repaired corroded column failed at 10.0% drift ratio. This demonstrates the effectiveness of the repair method. A numerical model was developed to simulate the seismic performance of the control, the corroded, and the repaired columns, which matched the experimental hysteresis curves and predicted fracture of longitudinal steel bars at the same drift ratio as the experiment. The numerical model is extended for parametric analysis of reinforced concrete columns with varying levels of corrosion and repaired columns.